Cultural and medical space design: case study - Mohd Nawawi, Norwina; Abdul Rahim, Zaiton; Hamat, Sufian (2018)
Geographically Malaysia lies in tropics with its own cases of tropical diseases. Malaysians, with about 30 million population are made up of many ethnic groups, culture and religion. Major ethnic are Malays (60%), Chinese (27%) and Indians(7%), Indigenous (6%), corresponding in general to Islam, Buddhist, Hindu and others respectively. The state of health as defined by WHO includes mind, body and spirit. Thence, the design of healthcare facilities for the general Malaysians should address the needs of the environment and culture as well as their respective faith which many researchers believe brings positive results to man’s overall well-being. Current designs attempt to bridge but focus only on the non-clinical area as culturally cohesive. This study aims to explore the extent how ‘culture’ in both clinical and non-clinical environment within selected healthcare facilities or space as case studies could be approached with the aim of highlighting cultural consideration in design as another important dimension to facilitate health and well being of the population. Using qualitative method of research through literature review, primary and secondary data, experiences and POE observations, the study had identified needs of the population as the ‘cultural elements’ that requires recognition and commitment by the Ministry of Health Malaysia to realise WHO’s inspiration of designing healthcare facilities not only to clinical functionality but in accordance to the culture of the locality.